Theoretical and Experimental Investigations on 20 Inches Threaded Casing Connections Failure under Field Conditions - Zisopol, D. G.; Minescu, M.; Badicioiu, M.; Caltaru, M. M. (Engineering, Technology & Applied Science Research, 2021)
This paper brings forward the results of theoretical and experimental investigations performed to determine the causes that led to the failure of 20 inches threaded casing connections during the tubing of the Lupşa Sat No. 1 oil well, Romania. The failure occurred due to the breakout of the threaded casing connections assembled in the factory. In order to establish the main causes of failure, theoretical investigations were taken into consideration to highlight the influence of the thread element errors on the correct make-up casing pin–coupling (box) conditions and to the axial tensile strength of the threaded casing connection. In addition, experimental investigations were performed on the failure casing connections, consisted of measuring the dimensional characteristics of the thread elements to determine the performance and monitor the technical condition of the tubular material used in the petroleum industry.